Faktor-faktor yang mempengaruhi kebolehan kepintaran emosi pekerja-pekerja sokongan di Malaysia Airports Sdn. Bhd. Kuching - Hajijah, bte. Mohd Reduan Lee. (Universiti Malaysia Sarawak (UNIMAS), 2005)
TIris study includes 70 respondents from the supportive staffat Malaysia Airports Berhod Kuching, Sarawak. The purpose ofthis study ;s to analyze the factors that ittIwnce the level of emotional intelligence among supportive staff. The random sampling method has been chosen in this study. The result ofthis study shows that the support staff at Malaysia Airports Sdn Berhad has medium level of emotional inteOigence.